Post 2015: setting up a coherent accountability framework - Heiner Janus; Niels Keijzer (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
United Nations (UN) deliberations are underway towards a post-2015 agenda that unites poverty eradication and sustainable development. While negotiators are tasked to determine goals and indicators, another fundamental question is: How will progress towards the sustainable development goals (SDGs) be monitored and reviewed? A post-2015 accountability framework is needed to document and guide how stakeholders take responsibility, learn from their efforts and adjust their behaviour towards achieving the SDGs in a transparent manner. Discussions on such a framework are still at an early stage. Only some general elements of an accountability framework have been agreed among UN Member States. Most importantly, the framework will be voluntary, non-binding and state-led, which raises the question of how governments and other actors can be incentivised to participate. The main incentives are likely to be reputational: states can strengthen their SDG profiles and showcase “best-practices”. They could also benefit through exchanging lessons learnt. Financial support, capacity development support and technology transfer can be additional incentives, particularly for least developed countries. Incentives, however, have to be complemented by a strong commitment and ownership at the national level. The framework should be rooted in an inclusive, bottom-up approach, in which each government determines its own level of ambition. Further, governments should be able to link their national efforts to SDG discussions at the regional and international levels in a multi-layered framework. Currently, a fragmented landscape of international bodies is dealing with individual elements of the proposed SDGs. For each of the 17 goals, myriad entities and platforms exist, both within and outside the UN system. All claim global coordination functions, but many continue to work in parallel. Without addressing this incoherence, the accountability framework risks becoming a loose collection of disconnected efforts. Such a patchwork approach will not suffice in supporting the realisation of an aspiring agenda. Therefore, the post-2015 discussions offer the unique opportunity of setting up a coherent accountability framework that engages stakeholders across all platforms. Such a framework would help to avoid duplication and promote synergies. Its major benefit is to bring key stakeholders together in a few focused discussions that are more effective and legitimate than the current fragmented setup of international cooperation. A coherent framework would feature improved monitoring and reporting as compared to the Millennium Development Goals (MDGs) and would enable a strengthened review process. It should consist of three key components: key actors (governments, the UN system, other stakeholders), interlinkages (within UN structures and outside of them) and ambition (in design and commitments). The international community should engage in discussions on the accountability framework without delay. Only then can the post-2015 agenda be placed on solid footing from the start.
Keywords: 330; Regionale + globale + transnationale Governance